The Greek Economic Crisis, Labor Markets and Policies - Vasiliki Bozani; Nick Drydakis (Vierteljahrshefte zur Wirtschaftsforschung, 2015)
The historic decision at the Euro Summit on July 12, 2015, to continue supporting Greece as a member of the EU and the euro family, provided Greece the chance to return to growth and sustainability, provided it takes the necessary steps to continue with its reforms. Jointly the Greek government with its partners (European Commission, European Central Bank and the International Monetary Fund), agreed that the success of economic policy decisions would be determined by the concentration on social policies. Policy initiatives should view reforms not as a debate between more versus less regulation, but rather as a matter of good versus bad regulation. Encouraging productive investment represents one of the main engines to sustain not just recovery but also promote productive transformations. Moreover one of the most pressing priorities for the Greek government should be to provide immediate support to vulnerable groups, to help alleviate the impact of the economic crisis, and set the stage for stable future economic growth.
Keywords: E24; E50; J01; J01; O52; 330; Economic crisis; labor markets; policies